2014
DOI: 10.1371/journal.pone.0094785
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change on Twitter: Topics, Communities and Conversations about the 2013 IPCC Working Group 1 Report

Abstract: In September 2013 the Intergovernmental Panel on Climate Change published its Working Group 1 report, the first comprehensive assessment of physical climate science in six years, constituting a critical event in the societal debate about climate change. This paper analyses the nature of this debate in one public forum: Twitter. Using statistical methods, tweets were analyzed to discover the hashtags used when people tweeted about the IPCC report, and how Twitter users formed communities around their conversati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
177
1
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 229 publications
(213 citation statements)
references
References 32 publications
3
177
1
13
Order By: Relevance
“…This idea has also been understood in relation to "selective exposure," a practice in which users seek opinionreinforcing content or demonstrate "challenge-aversion" which is seen as problematic and an "anathema to the deliberative perspective" (Freelon, 2013, p. 5;Sunstein, 2009). This idea is supported by Pearce, Holmberg, Hellsten, and Nerlich (2014), who found that Twitter users are more likely to make conversational connections with those who have broadly similar views. There is, however, a possibility that a larger "argument repertoire" increases ambivalence amongst participants.…”
Section: Deliberationmentioning
confidence: 82%
“…This idea has also been understood in relation to "selective exposure," a practice in which users seek opinionreinforcing content or demonstrate "challenge-aversion" which is seen as problematic and an "anathema to the deliberative perspective" (Freelon, 2013, p. 5;Sunstein, 2009). This idea is supported by Pearce, Holmberg, Hellsten, and Nerlich (2014), who found that Twitter users are more likely to make conversational connections with those who have broadly similar views. There is, however, a possibility that a larger "argument repertoire" increases ambivalence amongst participants.…”
Section: Deliberationmentioning
confidence: 82%
“…Marres (2017, p. 123) identifies three issues in digital bias (at a minimum) requiring attention: (1) bias in the selected data and content, as the researcher selects certain snapshots of social media coverage; (2) built-in software bias in the research instruments, for example, bias through embedded algorithms; and (3) bias of methodological nature, for example, social media research tools are more amenable to textual queries than visual queries, resulting in a bias towards textual analysis that provides only partial analysis of platform content. Marres calls for an 'affirmative approach' to digital bias (2017, p. 125); that is, accepting these biases as part of the object of study rather than attempting to neutralise platform effects by disentangling medium research from social research (Pearce, Holmberg, Hellsten, & Nerlich, 2014).…”
Section: Challenges To Cross-platform Research: Collapsed Objects Andmentioning
confidence: 99%
“…Sabe-se que a realização de eventos internacionais, as agendas intergovernamentais, as publicações de lideranças políticas e/ou pessoas famosas e os eventos meteorológicos extremos proporcionam um aumento nas abordagens não só na mídia tradicional como também nas referências ao tema nas redes sociais (Kirilenko & Stepchenkova, 2014;Pearce et al, 2014;Cody et al, 2015). está acontecendo?".…”
Section: Breve Revisão Da Literaturaunclassified
“…A preferência pelo uso de hashtag vai ao encontro do que muitos autores referem sobre a formação de "comunidades" ao utilizarem-se termos em comum (e.g. Segerberg & Bennett, 2011;Pearce et al, 2014;Williams et al, 2015). Identifica-se também que do total de publicações que utilizaram o termo "COP21" na língua espanhola, menos de um terço dos tweets é de texto original, sendo a maior parte partilha via RT.…”
Section: Volume De Publicaçõesunclassified